PENGARUH PARTISIPASI, SASARAN DAN PENEKANAN ANGGARAN TERHADAP KESENJANGAN ANGGARAN (STUDI PADA OPD KOTA LANGSA) - Riska Saprita; Nurlina; Nasrul kahfi Lubis (Jurnal Mahasiswa Akuntansi Samudra, 2023)
The purpose of this study is to determine the effect of participation, targets and budget emphasis on budget gaps in OPD Langsa City. The sample in this study amounted to 90 respondents. The data analysis method uses multiple linear regression analysis, and the tests used are the t test, F test and the coefficient of determination test. The results of the study show that budget participation has a significant effect on the budget gap in Langsa City OPD, budget targets have no significant effect on budget gaps in Langsa City OPD, budget emphasis has a significant effect on budget gaps in Langsa City OPD, participation, targets and budget emphasis simultaneously have an effect significantly to the budget gap in OPD Langsa City